Establishing a strategic framework of green procurement for the malaysian construction industry / Mohd Sallehuddin Mat Noor and Fadzil Hassan - Mohd Sallehuddin, Mat Noor; Fadzil, Hassan (2015)
Resource depletion has become the main issues in the last decades. The fact that world population increased into 7 billion in the year 2013, natural resources has become a crucial element in creating better quality of life through physical infrastructure development. In order to decrease the emission of carbon up to 20 percent in the year 2020, green procurement is believed to be one of the solution minimize the environmental impact through its nature of procuring service or product which can be controlled from the initiation steps until its demolition. The current problem in Malaysian construction industry is that it is at the junction in determining the growth of this sector. Megatrend in the global scale had influenced it through risk management, sustaining profitability, sustaining corporate social responsibility and growing bureaucracy, green procurement is believed to be the solution to the construction industry to grow steadily thus contributes to the nation’s economic and social growth. Most of the data that will be obtained are primary data, using document analysis, questionnaire and focus group that will be conducted to the respective bodies in construction industries. This research will be detailed up on its elements and the sub elements of the strategic framework within each element. It also will be tested in the real construction industry. Finally, this strategic framework will be validated to be used in the current industry. The anticipated finding is that to fill the knowledge gap by introducing a green procurement strategic framework for the industry restructuring a new type of procurement method.